2020
DOI: 10.1177/0003319720912935
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Hepatocyte Growth Factor and Risk of Incident Peripheral Artery Disease: The Multi-Ethnic Study of Atherosclerosis

Abstract: Higher levels of hepatocyte growth factor (HGF) have been associated with the presence of peripheral arterial disease (PAD), but prospective associations are unknown. We examined the association of circulating HGF levels with incident PAD. Between 2000 and 2002, HGF was measured in 6742 Multi-Ethnic Study of Atherosclerosis participants without PAD. Incident clinical PAD, adjudicated on the basis of a positive history for the presence of disease-related symptoms or treatment, was ascertained through 2015. Inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In this scenario, plasma biomarkers, only requiring one blood sample collection, yielded promising results in the prediction of both atherosclerosis extension and/or incident CVD events (12)(13)(14)(15)(16) . Plausible biomarkers include several circulating proteins that are involved in different pathogenic steps of the atherosclerotic plaque development, such as matrix metalloproteinases (MMPs) (17)(18)(19) , smooth muscle cells (SMC) (20)(21)(22)(23) and endothelial cells (EC) (20,(24)(25)(26)(27) growth factors (GFs), as well as mediators of apoptosis (20,(28)(29)(30)(31) and inflammation (20,32,33) . However, available studies focused on small subsets of these biomarkers and/or did not consider the complex interrelationship among them.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, plasma biomarkers, only requiring one blood sample collection, yielded promising results in the prediction of both atherosclerosis extension and/or incident CVD events (12)(13)(14)(15)(16) . Plausible biomarkers include several circulating proteins that are involved in different pathogenic steps of the atherosclerotic plaque development, such as matrix metalloproteinases (MMPs) (17)(18)(19) , smooth muscle cells (SMC) (20)(21)(22)(23) and endothelial cells (EC) (20,(24)(25)(26)(27) growth factors (GFs), as well as mediators of apoptosis (20,(28)(29)(30)(31) and inflammation (20,32,33) . However, available studies focused on small subsets of these biomarkers and/or did not consider the complex interrelationship among them.…”
Section: Introductionmentioning
confidence: 99%
“…Lowering IL-6 concentrations by targeting the upstream pathway with canakinumab was associated with a lower rate of cardiovascular events, independent of lipid-lowering, highlighting the substantial pathophysiological consequences of IL-6 for CVD [23]. Increased serum HGF has also been linked with cardiovascular complications, including myocardial infarction, congestive HF, ischemic retinopathy, and peripheral arterial disease [24][25][26][27]. In addition to IL-6 and HGF, CSF-1, ADA, IL-12B, TRANCE, and AXIN1 were also positively associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…There is some conflicting literature regarding the direction of the association between HGF levels and PAD. Garg and colleagues (2020) found that elevated HGF levels were correlated with a higher risk of PAD development [ 38 ]. In contrast, multiple investigations have shown the effectiveness of transfecting pro-angiogenic HGF plasmid DNA into patients with PAD to improve clinical outcomes [ [39] , [40] , [41] ].…”
Section: Discussionmentioning
confidence: 99%